PERFORMANCE ASSESSMENT OF ISLAMIC BANKS IN THE LIGHT OF MAQASID AL-SHARIAH: A GLOBAL EVIDENCE - Ammar, Asma (International Journal of Islamic Banking and Finance Research, 2023)
As an “Islamic” entity, Islamic banks are expected to fulfill the purposes of Islamic law. This study aims to assess the performance of Islamic banks beyond traditional yardsticks, to emphasize their ethical, social, and environmental role in accordance with the higher goals of Islamic law namely Maqasid al-Shariah. Based on Imam al-Ghazali’s concept of Maqasid al-Shariah, we develop a Maqasid al-Shariah index including the 5 objectives of Shariah (Preservation of Life, Religion, Intellect, Posterity, and Wealth). Sekaran’s operationalization method is used to transform the theoretical concept of Maqasid al-Shariah into measurable indicators. The originality of this study stems from two factors: First, we build on previous research to develop a new Maqasid al-Shariah index with 12 dimensions, 25 elements, and 25 indicators. Second, we provide fresh insight into the Maqasid al-Shariah performance of 10 large and well-established Islamic banks from 2017 to 2021. The results of the 5-year study show that Meezan Bank in Pakistan performed the highest score, while Dubai Islamic Bank received the lowest. Furthermore, when comparing the performance of the sampled Islamic banks across the five objectives, we find that they earned the lowest score in the objective of intellect due to their failure to disclose the required information in their annual reports.JEL Classification Codes: A13, G21, I31, L20, P47.